2004
DOI: 10.5694/j.1326-5377.2004.tb06234.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns for cancer in Western Australia: does being Indigenous make a difference?

Abstract: Objective: To examine whether hospital patients with cancer who were identified as Indigenous were as likely to receive surgery for the cancer as non‐Indigenous patients. Design, setting and patients: Epidemiological survey of all Western Australian (WA) patients who had a cancer registration in the state‐based WA Record Linkage Project that mentioned cancer of the breast (1982–2000) or cancer of the lung or prostate (1982–2001). Main outcome measures: The likelihoods of receiving breast‐conserving surgery or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 9 publications
7
41
0
Order By: Relevance
“…Our findings regarding treatment parallel reports from a number of international [22-24] and local [6,25-27] studies. We found that irrespective of remoteness or socioeconomic advantage, Indigenous people received less treatment than non-Indigenous counterparts (including Indigenous people who were most advantaged).…”
Section: Discussionsupporting
confidence: 88%
“…Our findings regarding treatment parallel reports from a number of international [22-24] and local [6,25-27] studies. We found that irrespective of remoteness or socioeconomic advantage, Indigenous people received less treatment than non-Indigenous counterparts (including Indigenous people who were most advantaged).…”
Section: Discussionsupporting
confidence: 88%
“…How this compares with other Indigenous populations with head and neck cancer is not known as no similar published data are available. However, treatment bias among Indigenous people with cancer in general, and with other specific cancers, has been reported in a number of studies [1,15-17]. The reasons why Indigenous people in this study were less likely to receive treatment are not precisely known but we found that those Indigenous people who do not receive treatment were likely to be older, male and socially disadvantaged compared to non-Indigenous people who did not receive treatment.…”
Section: Discussionmentioning
confidence: 50%
“…In general these details were not available from the medical records, and are therefore not assessed in this study. Reports suggest factors such as late stage at diagnosis [17], greater prevalence of comorbidities [1] and disparate treatment decisions made by health professionals based on assumptions about socioeconomic and cultural factors [21] may explain some of the treatment differential, but reports are not conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Late presentation and poor survival is also influenced by communication and cultural barriers which may impact the effectiveness and choice of treatment, as well as the decision to engage in preventive and diagnostic activities including cancer screening [19,20,33]. The presence of other chronic diseases or environmental conditions also limits provision of treatment due to the risk of complications [4,21,26,34].…”
Section: Methods and Resultsmentioning
confidence: 99%